2010
DOI: 10.3928/15428877-20100910-02
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Laser Trabeculoplasty

Abstract: Patterned laser trabeculoplasty provides rapid, precise, and minimally traumatic (sub-visible) computer-guided treatment with exact abutment of the patterns, exhibiting a 24% reduction in intraocular pressure during 6 months of follow-up (P < .01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…The single clinical study for PLT reported 24% average IOP reduction during 6 months of followup. 16 Widening of inter-trabecular spaces could account for this IOP reduction although the exact mechanism has not been determined. However, the study also reported a success rate at 6 months after the PLT treatment was 60% and one retreated case returned to the baseline IOP at 5 months.…”
Section: Trabecular Meshwork After Laser Trabeculoplasty 911mentioning
confidence: 98%
See 4 more Smart Citations
“…The single clinical study for PLT reported 24% average IOP reduction during 6 months of followup. 16 Widening of inter-trabecular spaces could account for this IOP reduction although the exact mechanism has not been determined. However, the study also reported a success rate at 6 months after the PLT treatment was 60% and one retreated case returned to the baseline IOP at 5 months.…”
Section: Trabecular Meshwork After Laser Trabeculoplasty 911mentioning
confidence: 98%
“…The laser was applied in the predetermined pattern of 66 spots comprised of three arcs of 100 mm-sized spots using 5 ms of automatically reduced pulse duration. 16 This procedure was repeated to cover 360 degrees of the trabecular meshwork, taking care not to duplicate the spot pattern. Two cats were sacrificed by placing them in a carbon dioxide chamber at each of three time points (1, 4 and 9 weeks) following laser treatment for light microscopy (LM) and scanning electron microscopy (SEM) One untreated cat served as the control and this cat was sacrificed in the same manner at 9 weeks.…”
Section: Laser Trabeculoplastymentioning
confidence: 99%
See 3 more Smart Citations